Experimental study on the prediction model of the cumulative strain of the soil–rock mixture backfill under metro train load. Issue 3 (October 2020) - Zhong, Z L; Xu, Y W; Hu, X X; Liu, X R; Du, L B
Abstract: An indoor dynamic triaxial test was performed on the soil–rock mixture (SRM) backfill in Chongqing to study the cumulative strain characteristics of the SRM under the cyclic dynamic loading of the metro train. The effects of different consolidation degrees U, rock block contents P, and effective consolidation confining pressures σ 3 ′ were then analyzed. Results showed that when σ 3 ′ and P are the same, the lower the U, the faster will be the increase in cumulative strain. When U and P were the same, the lower the σ 3 ′, the greater will be the increase in cumulative strain and the higher will be the cumulative strain stable value of the stability curve. When U and σ 3 ′ were the same, the lower the P, the faster will be the increase in cumulative strain. An empirical model of the cumulative strain of the SRM considering the influence of U, P, and σ 3 ′ was established on the basis of the results of the dynamic triaxial tests. The accuracy of the prediction model was verified against the actual test results. This study provides a theoretical basis for the settlement and deformation evaluation of SRM backfill subgrades under metro train cyclic loading.